Natural History of Untreated Transverse/Sigmoid Sinus Thrombosis Following Posterior Fossa Surgery: Case Series and Literature Review. Issue 2 (19th December 2019) - Orlev, Alon; Jackson, Christopher M; Luksik, Andrew; Garzon-Muvdi, Tomas; Yang, Wuyang; Chien, Wade; Harnof, Sagi; Tamargo, Rafael J
Abstract: BACKGROUND: Transverse or sigmoid sinus thrombosis occurs in 4% to 11% of patients following posterior fossa surgery. Anticoagulation has been the mainstay treatment, mostly based on extrapolation from the literature on spontaneous sinus thrombosis. OBJECTIVE: To analyze the rate and associated complications of postoperative transverse/sigmoid sinus thrombosis for patients undergoing posterior fossa tumor resection. In this series, no antithrombotic therapy was initiated, and no postoperative treatment alterations were made following thrombosis diagnosis. METHODS: Prospectively accrued cases from a single surgeon operating at a single academic center were retrospectively reviewed to determine the natural history of untreated transverse/sigmoid sinus thrombosis following posterior fossa surgery. Inclusion criteria were patients 18 yr or older undergoing resection of a posterior fossa tumor. A total of 538 patients were analyzed. RESULTS: In all 26 out of 538 (4.8%) patients were diagnosed with transverse/sigmoid sinus thrombosis on routine postoperative imaging. Early postoperative complication rate was 38% in the sinus thrombosis group, as compared to 15% in the no-thrombosis group ( P = .02). A significantly higher rate of pseudomeningocele, dysphagia requiring gastrostomy, and cerebellar stroke signs were noted in patients with postoperative sinus thrombosis. However, only 3 of the 26 patients (12%) with postoperative sinus occlusion suffered prolonged central nervous system complications. CONCLUSION: Transverse/sigmoid sinus thrombosis following suboccipital craniectomy results in a higher rate of early complications; however, most of these complications resolve without anticoagulation. It may be reasonable, therefore, to manage these patients conservatively in order to avoid the risks associated with anticoagulation in the perioperative period. Graphical Abstract: